Activities of Daily Living, Playfulness and Sensory Processing in Children with Autism Spectrum Disorder: A Spanish Study - Nuria Yela-González; Montserrat Santamaría-Vázquez; Juan Hilario Ortiz-Huerta (Children, 2021)
The purposes of the study were to identify whether differences exist between Spanish children with ASD and neurotypical development in relation to Activities of Daily Living (ADL), playfulness, and sensory processing; as well as to confirm whether a relation exists between those areas and sensory processing. Study Design: A descriptive cross-sectional study. Methods: Forty children, 20 with a diagnosis of ASD and 20 with neurotypical development, were recruited. The measurement tools used were the Pediatric Evaluation of Disability Inventory (PEDI), Test of Playfulness (ToP), and Sensory Processing Measure (SPM). Results: The sensory processing of children with ASD were related to decreased functional skills performance of ADL (F = 94.4, p = 0.00) and playfulness (p = 0.00) than neurotypical children; in addition, the problems of sensory reactivity were associated with worse development in these occupational areas (p = 0.00 for both Spearman correlations). Conclusions: Children with ASD present worse performance of functional skills and playfulness than neurotypical ones. Likewise, sensory reactivity is related to the development in the occupational areas.